Challenges in sarcoidosis and sarcoid‐like reactions associated to immune checkpoint inhibitors: A narrative review apropos of a case. Issue 1 (10th December 2020) - Apalla, Zoe; Kemanetzi, Christina; Papageorgiou, Chryssoula; Bobos, Mattheos; Manoli, Magdalini; Fotiadou, Christina; Hatzibougias, Dimitrios; Boukovinas, Ioannis; Stergiou, Eleni; Levva, Sofia; Lallas, Aimilios; Lazaridou, Elizabeth
Abstract: Sarcoidosis and sarcoid‐like reactions (SLRs) may develop in association with various malignancies, as well as in association to certain oncologic drugs, including immune checkpoint inhibitors (ICIs). We aimed to perform a narrative review with regard to the development of ICIs‐associated sarcoidosis or SLRs, and to discuss the corresponding diagnostic and therapeutic challenges raised in this scenario. Apropos of a melanoma patient developing SLRs while treated with ipilimumab and nivolumab, we searched for clinically evident, ICIs‐associated sarcoidosis or SLRs in the English literature. We recorded the oncologic characteristics, including type of malignancy and type of ICI, the phenotypic characteristics of sarcoidosis/SLRs, as well as the impact on immunotherapy. Including our patient, we identified 80 ICIs‐associated sarcoidosis or SLRs cases. Both sexes were equally affected (40 F/40 M) and the most common malignancy was melanoma (65/80, 81.3%). Concerning the oncologic treatment, there was a predilection for pembrolizumab (23/80, 28.7%), followed by the ipilimumab/nivolumab combination (21/80, 26.3%), ipilimumab (18/80, 22.5%), nivolumab (16/80, 20.0%). Although in the majority of the cases (52/80, 65.0%) there was no need for systemic prednisolone for the management of sarcoidosis, a significant proportion of patients finally discontinued ICIs treatment (44/80, 55.0%). Phenotypically, sarcoidosis and SLRs highly imitate oncologic progression posing diagnostic difficulties. A therapeutic dilemma is also raised when there is a need for systemic prednisolone, since the latter may jeopardize the therapeutic efficacy of immunotherapy. Sarcoidosis and SLRs, though rare, can present in oncologic patients treated with ICIs. Clinicians should be aware of this possibility and the related diagnostic and therapeutic challenges they have to face in this scenario.